Effect of Hydroxychloroquine Therapy on Hematology and Ocular Manifestations of Systemic Lupus Erythematosus Patients - Muhsin, Muhsin; Sylvawani, Mahriani; Abdullah, Vera; Nilawati, Enny; Riswan, Muhammad; Abdullah, Abdullah; Syukri, Maimun (eJournal Kedokteran Indonesia, 2025)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that mainly affects women and has various clinical manifestations involving multiple organs. The use of hydroxychloroquine (HCQ) provides some advantages. This study aimed to analyze hematological and ocular effects following short-term HCQ administration in SLE patients. A cross-sectional study was conducted from April to July 2022 at Zainoel Abidin Hospital, Banda Aceh, Indonesia, involving 23 female SLE patients. Blood laboratory parameters were assessed, and an ophthalmologist performed ocular examinations. The study showed an average hemoglobin of 11.6 g/dL. Other blood laboratory results were within normal limits. The mean duration of SLE diagnosis and HCQ use was 21.0 months and 9.7 months, respectively. There was no correlation between HCQ use duration and hematological parameters (hemoglobin, leukocytes, and thrombocytes; p values 0.38, 0.14, and 0.62, respectively). This study showed that only one SLE patient taking HCQ for less than five years had ocular problems. The prevalence of ocular and hematological effects in SLE patients treated with HCQ for less than five years is minimal.